Pandangan Kognitif Tentang Belajar: Array - Ahmad Zakki; Neviyarni; Herman Nirwana (eductum: Jurnal Literasi Pendidikan, 2022)
This study focuses on a cognitive view of the development and learning process experienced by each individual. The basic cognitive study is neurological science (neuroscience). Each nerve in the brain has its own role in doing its job. According to this view, learning is the process of creating and strengthening new pathways of connection between nerves to the brain or what is called synapse. With this synapse connected to new nerves, humans will learn. In cognitive, learning is a long-lasting change in perception and understanding. The learning model introduced by cognitive is the information processing model, while the information processing model is long term memory, sort term memory, and metacognition.